2007
DOI: 10.2341/06-134
|View full text |Cite
|
Sign up to set email alerts
|

Amalgam and Composite Posterior Restorations: Curriculum Versus Practice in Operative Dentistry at a US Dental School

Abstract: SUMMARYThis study recorded the number of preclinical lecture and simulation laboratory sessions spent teaching the preparation and placement of amalgam and resin composite posterior restorations. These data were compared to the use of both materials in the operative clinic as placed by third-and fourth-year students. The number of posterior restorations inserted by the students, expressed as a function of the number of restoration surfaces, was also evaluated. The results show that the teaching of posterior re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 11 publications
0
25
0
3
Order By: Relevance
“…One explanation may be that placing composite fillings is more operator sensitive than amalgam fillings and that most of the GPs are more familiar with amalgam than with composite materials. In a study by Ottenga and Mjör [2007], the number of preclinical lectures and laboratory sessions that was spent teaching the preparation and placement of amalgam and resin com-posite was recorded. These data were compared to the use of both materials in the operative clinic by third-and fourth-year students.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation may be that placing composite fillings is more operator sensitive than amalgam fillings and that most of the GPs are more familiar with amalgam than with composite materials. In a study by Ottenga and Mjör [2007], the number of preclinical lectures and laboratory sessions that was spent teaching the preparation and placement of amalgam and resin com-posite was recorded. These data were compared to the use of both materials in the operative clinic by third-and fourth-year students.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that the indications, contraindications and techniques taught for posterior composite restorations vary widely among dental schools [7] .…”
mentioning
confidence: 99%
“…Composite resins have proven to be predictable and reliable restorative materials for the treatment of traumatized dentin or dental caries in the anterior region 3,4) . Recent longevity data on resin-based restorations have shown that the quality and longevity of these materials have increased 5) . Against this background, they have been suggested as substitutes for amalgam to restore posterior teeth because of these advantages: they offer improved esthetics and they do not contain mercury [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent longevity data on resin-based restorations have shown that the quality and longevity of these materials have increased 5) . Against this background, they have been suggested as substitutes for amalgam to restore posterior teeth because of these advantages: they offer improved esthetics and they do not contain mercury [3][4][5] . On this note, it has been stated that 21 st century ultrafine compact-filled composite resins may be the materials of choice for restoring posterior cavities 2) .…”
Section: Introductionmentioning
confidence: 99%